Kepuasan Kerja sebagai Mediasi Pengaruh Kualitas Kehidupan Kerja terhadap Kinerja Karyawan pada Usaha Kafe di Kota Malang - Sandra Irawati; Khusnul Rofida Novianti (Journal of Management and Business Review, 2022)
This research tries to describe the quality of work-life, job satisfaction, and employee performance in cafe and restaurant businesses in Malang. Explain the influence of the quality of work-life on employee performance; the impact of the quality of work-life on employee job satisfaction; the effect of job satisfaction on employee performance; explain the role of the job satisfaction in mediating the influence of the quality of work-life on employee performance. Collected data were by distributing questionnaires to 100 cafe employees in the city of Malang. The analytical tool used is Path Analysis. The results showed that the cafe employees' work-life quality was in a good category. Employees feel satisfied concerning work, wages/salaries, working conditions, co-workers, and personal suitability with their work. The cafe employee's performance in terms of work processes is high. The quality of work-life has a significant positive effect on employee performance and job satisfaction. Then employee job satisfaction has a significant positive impact on employee performance. Job satisfaction significantly mediates the influence of the quality of work-life on employee performance.